Perkuatan Struktur Kolom Beton Bertulang Dengan Metode Concrete Jacketing - Balqis, Charla Putri; Bintang, Michael Chrisyie Daniel; Zulkifli, Zulkifli (Dept. of Civil Engineering Universitas Riau, 2024)
Reinforced concrete columns are critical structural elements that support vertical loads in buildings. Over time, these columns may experience a reduction in capacity due to aging, seismic activity, fire exposure, or changes in building function. Concrete jacketing is one of the most widely used strengthening techniques to restore and enhance the performance of damaged or weakened columns. This study presents a comprehensive literature review to evaluate the effectiveness of concrete jacketing in improving the axial, shear, and flexural capacities of reinforced concrete columns. The mechanism of this method is explained through the enlargement of the cross-sectional area, installation of additional reinforcement, and confinement effects. The review also explores material innovations such as the use of self-compacting concrete (SCC), the addition of fly ash, and alternative reinforcement materials like bamboo and natural fibers. Key implementation aspects, including surface preparation, reinforcement detailing, and casting methods, are also analyzed. Furthermore, the study compares concrete jacketing with other strengthening methods in terms of cost-effectiveness and applicability. The findings indicate that concrete jacketing is a practical, economical, and effective strengthening solution, particularly for buildings located in seismic-prone areas or undergoing functional changes.